Compliance with requirement to report results on the EU Clinical Trials Register: cohort study and web resource. (12th September 2018) - Goldacre, Ben; DeVito, Nicholas J; Heneghan, Carl; Irving, Francis; Bacon, Seb; Fleminger, Jessica; Curtis, Helen
Abstract: Objectives: To ascertain compliance rates with the European Commission's requirement that all trials on the EU Clinical Trials Register (EUCTR) post results to the registry within 12 months of completion (final compliance date 21 December 2016); to identify features associated with non-compliance; to rank sponsors by compliance; and to build a tool for live ongoing audit of compliance. Design: Retrospective cohort study. Setting: EUCTR. Participants: 7274 of 11 531 trials listed as completed on EUCTR and where results could be established as due. Main outcome measure: Publication of results on EUCTR. Results: Of 7274 trials where results were due, 49.5% (95% confidence interval 48.4% to 50.7%) reported results. Trials with a commercial sponsor were substantially more likely to post results than those with a non-commercial sponsor (68.1% v 11.0%, adjusted odds ratio 23.2, 95% confidence interval 19.2 to 28.2); as were trials by a sponsor who conducted a large number of trials (77.9% v 18.4%, adjusted odds ratio 18.4, 15.3 to 22.1). More recent trials were more likely to report results (per year odds ratio 1.05, 95% confidence interval 1.03 to 1.07). Extensive evidence was found of errors, omissions, and contradictory entries in EUCTR data that prevented ascertainment of compliance for some trials. Conclusions: Compliance with the European Commission requirement for all trials to post results on to the EUCTR within 12 months of completion has been poor, with half of all trials non-compliant. EU registry data commonly contain inconsistencies that might prevent even regulators assessing compliance. Accessible and timely information on the compliance status of each individual trial and sponsor may help to improve reporting rates.